2017
DOI: 10.1016/j.bbmt.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Infections of the Central Nervous System after Unrelated Donor Umbilical Cord Blood Transplantation or Human Leukocyte Antigen–Matched Sibling Transplantation

Abstract: We analyzed the incidence, clinical characteristics, prognostic factors, and outcome of central nervous system (CNS) infections in consecutive patients with receiving umbilical cord blood transplantation (UCBT) (n = 343) or HLA-matched sibling donor stem cell transplantation (MST) (n = 366). Thirty-four CNS infections were documented at a median time of 116 days after transplantation (range, 7 to 1161). The cumulative incidence (CI) risk of developing a CNS infection was .6% at day +30, 2.3% at day +90, and 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In fact, in the 34 centres participating in this study, less than 1 case per centre per year was observed. With regard to the underlying haematological disease, most of the cases were observed in patients with AML and ALL or in recipients of an allogeneic SCT . In most cases, patients had an active disease at the time of the onset of IFI while few cases occurred with a haematological disease in remission or during the consolidation phase.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the 34 centres participating in this study, less than 1 case per centre per year was observed. With regard to the underlying haematological disease, most of the cases were observed in patients with AML and ALL or in recipients of an allogeneic SCT . In most cases, patients had an active disease at the time of the onset of IFI while few cases occurred with a haematological disease in remission or during the consolidation phase.…”
Section: Discussionmentioning
confidence: 99%
“…We found 36 L. prolificans invasive infections in HSCT recipients, including our report. Seven of them were included in case series and individual data were not available . The remaining 29 cases are described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Seven of them were included in case series and individual data were not available. 7,[15][16][17] The remaining 29 cases are described in Table 1. There were 6 cases (20.7%) of locally invasive infection, 10 cases of isolated fungemia (34.5%), and 13 cases of disseminated disease (44.8%).…”
Section: Literature Search On Lomentospora Prolificans After Hsctmentioning
confidence: 99%
“…66 Interestingly, it was also noted that patients who underwent UC-BSCs transplantation were more prone to CNS infections. 67…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%